NILAI PATRIOTISME DALAM NOVEL KELUARGA GERILJA DAN IMPLEMENTASINYA SEBAGAI PEMBELAJARAN DI SEKOLAH - Amanda Kalalo, Artha Jeane Claudya Amanda Kalalo, Ahadi; Sulissusiawan, Ahadi; Priyadi, A Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the desire to apply the value of patriotism to students through the novel Gerilja Keluarga by Pramoedya Ananta Toer. The common problem in this research is